The concept of native photography by Jan Bułhak in the context of modern aesthetic education - Wojciech Bobrowicz (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
This article is devoted to the concept of native photography created by Jan Bułhak in the 1930s and 1940s. This concept covers the idea of combining the aesthetics of landscape photography with the issue of patriotic education realized by the pictures of the homeland. The idea of native photography is transposed into modern times and the ubiquity of digital photography in new media, especially in social media.